American microelectronics data annual. - Dummer, G. W. A. (Geoffrey William Arnold); Robertson, J. Mackenzie (Pergamon Press, 1964)
American Microelectronics Data Annual 1964-65 provides comprehensive information on different microelectronics available in the U.S.